ANALISIS PENGARUH KINERJA KEUANGAN PERUSAHAAN TERHADAP KAPITALISASI PASAR DAN NILAI PERUSAHAAN PADA PERUSAHAAN RETAIL DI BEI - Priyo Darmawan (Jurnal Akuntansi Bisnis, 2017)
Corporate performance measurement  is one of the critical aspects of determining invesment. Therefore, it is necessary to need for a proper measurement of enabling to assess accurately and sufficiently in order to investors and creditors misleadings. The objective of this research is to analysis financial performance of Economic Value Added (EVA), and Market Value Added (MVA), Total Shareholder Return (TSR) against market capitalization and corporate value. The applied method  in this research is using multiple regression and linier regression analysis to the      F-test,Tt-test, and classic regression assumption. The results of this reseach is referring to  the existence of  the impact of  EVA, MVA, TSR , ROE, ROA, EPS and PER on  market capitalization and corporate value. Key Word : Market Value Added (MVA), Tobin’s Q, ROA (Return On Asset), ROE (Return On Equity), Market Capitalization, Earning Per Share (EPS)